2014
DOI: 10.1107/s2053230x14008838
|View full text |Cite
|
Sign up to set email alerts
|

Complex assembly, crystallization and preliminary X-ray crystallographic analysis of the bovine CD8αα–BoLA-2*02201 complex

Abstract: In order to clarify the structural characteristics of the bovine MHC class I molecule (BoLA-I) complexed with CD8αα (CD8αα-BoLA-I), bovine CD8αα, BoLA-I (BoLA-2*02201) and β2m were expressed and purified, and were then assembled with a peptide derived from Foot-and-mouth disease virus (FMDV-VP1YY9) and crystallized. The crystal diffracted to 1.7 Å resolution and belonged to space group P21, with unit-cell parameters a=53.9, b=103.8, c=61.8 Å, α=γ=90, β=96°. The asymmetric unit contained one complex, with a Mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…These p/MHC I structures revealed that although the MHC I molecules from different animals have their own species-specific features, they have a similar overall architecture and structural basis to present peptides. However, no information about the crystal structures of chicken, swine and bovine CD8 molecules have been reported except the preliminary studies of these CD8 molecules by our group 40 41 42 .…”
mentioning
confidence: 99%
“…These p/MHC I structures revealed that although the MHC I molecules from different animals have their own species-specific features, they have a similar overall architecture and structural basis to present peptides. However, no information about the crystal structures of chicken, swine and bovine CD8 molecules have been reported except the preliminary studies of these CD8 molecules by our group 40 41 42 .…”
mentioning
confidence: 99%